(untitled) - Callister, William D. (New York, 2005)
This comprehensive introduction to Material Science is presented as a book/CD product that covers all core topics in print and includes five bonus chapters on CD. The CD provides a link to a companion website that includes interactive simulations and animations that related to key concepts and a materials selection database.
Hóa học chất rắn,Khoa học và Kỹ thuật vật liệu đại cương,Hóa học chất rắn,Khoa học và Kỹ thuật vật liệu đại cương
Keywords: Engineering materials